Preparation of pH-responsive mesoporous hydroxyapatite nanoparticles for intracellular controlled release of an anticancer drug. (20th October 2015) - Li, Dalong; Huang, Xin; Wu, Yadong; Li, Jiwei; Cheng, Weilu; He, Jinmei; Tian, Huayu; Huang, Yudong
Abstract : A well-defined core–shell nano-carrier (PAA–MHAPNs) was successfully synthesized based on a graft-onto method by using mesoporous hydroxyapatite nanoparticles (MHAPNs) as the core and polyacrylic acid (PAA) as the shell. Abstract : A well-defined core–shell nano-carrier (PAA–MHAPNs) was successfully synthesized based on a graft-onto method by using mesoporous hydroxyapatite nanoparticles (MHAPNs) as the core and polyacrylic acid (PAA) as the shell. Given that MHAPNs are regarded as one of the most promising drug delivery vehicles due to their excellent performance and the nature of their cancer cell anti-proliferative effect, and the grafted PAA, as a pH-responsive switch, could improve the loading amount of the drug doxorubicin hydrochloride (DOX) effectively by electrostatic interactions, all these advantages mean that the designed models show promise for application in pH-responsive drug delivery systems. The loading content and entrapment efficiency of DOX could reach up to 3.3% and 76%, respectively. The drug release levels of the constructed DOX@PAA–MHAPNs were low under normal physiological conditions (pH 7.4), but they could be increased significantly with a decrease of pH. Cytotoxicity assays indicated that the PAA–MHAPNs was biocompatible, and more importantly, the DOX@PAA–MHAPNs demonstrated an obvious ability to induce apoptosis of cancer cells. Overall, the synthesized systems should show great potential as drug nanovehicles with excellent biocompatibility, high drug loading, and pH-responsive features for future intracellular drug delivery.